Relationship between Peak Eccentric Force during the Nordic Hamstring Exercise and One Repetition Maximum Deadlift Performance - Satoru Nishida; Wataru Ito; Taisuke Ohishi; Riku Yoshida; Shigeru Sato; Masatoshi Nakamura (North American Sports Medicine Institute, 2024)
# Background The Nordic hamstring exercise (NHE) is useful for preventing hamstring strain injuries. However, its adoption rates in the sports field are currently low, necessitating a safe and efficient introduction. # Hypothesis/Purpose The purpose was to examine the relationship between the eccentric force during the NHE and the one repetition maximum of deadlift. It was hypothesized that the eccentric force during the NHE would be correlated with the one repetition maximum (1RM) of the deadlift. # Study design Cross-sectional study. # Methods Healthy student rugby players with no history of hamstring tears were recruited to participate. The peak eccentric forces during the NHE, which is the vertical peak force on the part holding the leg, were measured in both legs, while gradually leaning forward to a prone position over three seconds. The 1RM of deadlift was calculated from the weight that could be raised three times during a deadlift (x kg) using the estimated formula (x kg / 0.93). The correlation between the left and right peak eccentric forces during the NHE, the total left and right forces, and the 1RM of the deadlift was examined using Spearman's rank correlation coefficient, with all values corrected for body mass. # Results During the NHE, the peak eccentric force of the right and left legs and the total peak eccentric force of both legs were 3.8 ± 1.1 N/BM, 3.8 ± 1.2 N/BM, and 7.6 ± 2.1 N/BM, respectively. The 1RM of deadlift was 1.9 ± 0.3 kg/BM. Weak correlations (r = 0.34-0.37) were found between the 1RM of the deadlift and the peak eccentric force in the right and left legs and the total peak eccentric force of both legs. # Conclusion The present study revealed a weak correlation between the peak eccentric force during the NHE and 1RM of deadlift # Level of Evidence 2c